A Terracotta Figurine of a War Elephant and Other Finds from a Grave at Thessaloniki - Lambrothanassi , Eleni; Touloumtzidou, Annareta (Journal of Hellenistic Pottery and Material Culture, 2020)
A cist grave found in a western cemetery of Thessaloniki, in the region of Xirokrini, contained the remains of a boy, accompanied by pottery, iron strigils, a game board set, knuckle-bones, a bronze coin of Antigonus Gonatas, and terracotta figurines, including an exceptional war elephant. Grave goods are connected with the world of children, but also with the world and the activities of adults, like athletics, board games and war. The grave can be dated during the first years of Antigonus’ Gonatas reign, between 270 and 260 BCE, when war elephants and Gallic mercenaries were part of his army.